1977
DOI: 10.1073/pnas.74.5.2079
|View full text |Cite
|
Sign up to set email alerts
|

Localization of RNA polymerase in polytene chromosomes of Drosophila melanogaster.

Abstract: RNA polymerase (RNA nucleotidyltransferase) B (or II) and histone HI of Drosophila melanogaster were localized on salivary gland polytene chromosomes using the indirect immunofluorescence technique. RNA polymerase B is present almost exclusively in puffs and interband regions, whereas histone HI is found primarily in bands. The puff at region 3C, known to be transcriptionally active in larval salivary glands, gives a bright fluorescence with antibodies against RNA polymerase B. This fluorescence disappears aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(79 citation statements)
references
References 20 publications
10
67
2
Order By: Relevance
“…Previous studies using an anti-RNA Pol II serum (Jamrich et al 1977) indicated that the enzyme was located primarily in puffs and interbands, rather than in the bands that are more condensed and contain most of the DNA mass. To relate our current work to earlier experiments, we compared the anti-IIA and anti-II0 signals with a signal from DAPI, a fluorescent dye that binds to DNA and produces a pattern nearly identical to the classical banding pattern (e.g., see Fig.…”
Section: Rna Polymerase Is In Interbands and Puffsmentioning
confidence: 99%
“…Previous studies using an anti-RNA Pol II serum (Jamrich et al 1977) indicated that the enzyme was located primarily in puffs and interbands, rather than in the bands that are more condensed and contain most of the DNA mass. To relate our current work to earlier experiments, we compared the anti-IIA and anti-II0 signals with a signal from DAPI, a fluorescent dye that binds to DNA and produces a pattern nearly identical to the classical banding pattern (e.g., see Fig.…”
Section: Rna Polymerase Is In Interbands and Puffsmentioning
confidence: 99%
“…Moreover, RNA polymerase II appears to dissociate from these puffs and associates predominantly with heat shock puff sites (34,35). Chromosomal condensation (the puff to band transition) could participate in gene repression or simply be a consequence of gene repression.…”
Section: The Level Of Hsp 70 Poly(a) Rna Shows a Comparable Level Of mentioning
confidence: 99%
“…Gene induction varies according to conditions, but this rapid transcriptional response generates 10-fold to 1000-fold induction of Hsp genes within minutes of temperature elevation (Lindquist 1986). Simultaneously, heat shock results in down-regulation of normal transcription (Jamrich et al 1977), presumably to prevent accumulation of misfolded translation products (Lindquist 1986). These rapid genome-wide transcriptional responses make the heat-shock system ideal for investigating chromatin alterations that accompany gene regulatory changes.…”
mentioning
confidence: 99%